A cluster randomised controlled trial of smoking cessation in pregnant women comparing interventions based on the transtheoretical (stages of change) model to standard care. Issue 2 (1st June 2003) - Lawrence, T; Aveyard, P; Evans, O; Cheng, K K
Abstract : Objectives: To evaluate the effectiveness in helping pregnant women stop smoking of two interventions (Pro-Change for a healthy pregnancy) based on the transtheoretical model of behaviour change (TTM) compared to current standard care. Design: Cluster randomised trial. Setting: Antenatal clinics in West Midlands, UK general practices. Participants: 918 pregnant smokers Interventions: 100 general practices were randomised into the three trial arms. Midwives in these practices delivered three interventions: A (standard care), B (TTM based self help manuals), and C (TTM based self help manuals plus sessions with an interactive computer program giving individualised smoking cessation advice). Main outcome measures: Biochemically confirmed smoking cessation for 10 weeks previously, and point prevalence abstinence, both measured at 30 weeks of pregnancy and 10 days after delivery. Results: There were small differences between the TTM arms. Combining the two arms, the odds ratios at 30 weeks were 2.09 (95% confidence interval (CI) 0.90 to 4.85) for 10 week sustained abstinence and 2.92 (95% CI 1.42 to 6.03) for point prevalence abstinence relative to controls. At 10 days after delivery, the odds ratios were 2.81 (95% CI 1.11 to 7.13) and 1.85 (95% CI 1.00 to 3.41) for 10 week and point prevalence abstinence respectively. Conclusions: While there is a small borderline significant increase in quitting in the combined intervention arms compared with the controls, the effect of the intervention is small. At 30 weeks gestation and at 10 days postnatal, only about 3% of the intervention groups achieved sustained cessation, with numbers needed to treat of 67 (30 weeks of gestation) and 53 (10 weeks postnatal) for one additional woman to achieve sustained confirmed cessation. Given also that the intervention was resource intensive, it is of doubtful benefit.